2002
DOI: 10.1002/cbf.968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thymoquinone on antioxidant enzyme activities, lipid peroxidation and DT‐diaphorase in different tissues of mice: a possible mechanism of action

Abstract: The present investigation focused, firstly, on the effects of oral administration of thymoquinone (TQ) on antioxidant enzyme activities, lipid peroxidation and DT-diaphorase activity in hepatic, cardiac and kidney tissues of normal mice. Superoxide dismutase (SOD; E.C:1.15.1.1), catalase (CAT; E.C:1.11.1.6), glutathione peroxidase (GSH-Px; E.C:1.11.1.9), glutathione-S-transferase (GST; E.C:2.5.1.18), and DT-diaphorase (E.C:1.6.99.2) enzyme activities in each tissue type were determined. Treatment of mice with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
202
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(219 citation statements)
references
References 25 publications
13
202
0
4
Order By: Relevance
“…Several components of black cumin have been identified, including thymoquione, thymol, thymohydroquinone, and dithymquinone (2,3). Thymoquinone (TQ), the most abundant component of black seed oil, has been reported to exhibit antioxidant (4)(5)(6), antiinflammatory, and chemopreventive (7-9) effects. For instance, TQ has been shown to suppress the proliferation of various tumor cells, including colorectal carcinoma, breast adenocarcinoma, osteosarcoma, ovarian carcinoma, myeloblastic leukemia, and pancreatic carcinoma (7,(10)(11)(12)(13)(14), although it is minimally toxic to normal cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…Several components of black cumin have been identified, including thymoquione, thymol, thymohydroquinone, and dithymquinone (2,3). Thymoquinone (TQ), the most abundant component of black seed oil, has been reported to exhibit antioxidant (4)(5)(6), antiinflammatory, and chemopreventive (7-9) effects. For instance, TQ has been shown to suppress the proliferation of various tumor cells, including colorectal carcinoma, breast adenocarcinoma, osteosarcoma, ovarian carcinoma, myeloblastic leukemia, and pancreatic carcinoma (7,(10)(11)(12)(13)(14), although it is minimally toxic to normal cells (15).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, TQ is known to reduce oxidative stress not only through the direct antioxidant effect but also indirectly. Previous studies reported that TQ acted as a strong reactive oxygen species (ROS) scavenger (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Thymoquinone is reported to prevent oxidative injury in various in vitro and in vivo studies in rats (Daba and Abdel-Rahman, 1998;Mansour et al, 2001;Yaman and Balikci, 2010). Thymoquinone has been suggested to act as an antioxidant and was reported to prevent membrane lipid peroxidation in tissues (Mansour et al, 2002). These effects seem to be related to inhibition of eicosanoid generation, namely thromboxane B2 and leucotrienes B4 (by inhibiting cyclooxygenase and 5-lipooxygenase, respectively), and membrane lipid peroxidation (Hosseinzadeh et al, 2007).…”
mentioning
confidence: 99%